ANASTREPHA FRUIT FLIES (DIPTERA, TEPHRITIDAE) FROM TWO MUNICIPALITIES OF THE STATE OF RORAIMA, BRAZIL, WITH THREE NEW RECORDS - Marsaro JÃºnior, Alberto Luiz; Adaime, Ricardo; Souza-Filho, Miguel Francisco de; Lima, Camila Ribeiro; Trassato, Luiz Carlos (REVISTA DE AGRICULTURA, 2013)
We collected fruit flies in McPhail traps in two municipalities of the state of Roraima, Brazil. In Amajari we collected five Anastrepha species (including a probable new species) and in Boa Vista we collected 10 species. This is the first report of Anastrepha fractura Stone, Anastrepha fraterculus (Wiedemann) and Anastrepha longicaudaLima in the state of Roraima.